THE EFFECT OF BREASTMILK TOPICAL ON PERINEAL WOUND HEALING ON 1-7 DAYS POSTPARTUM MOTHE - Shinta Nuraini; Siti Saadah; Sariestya Rismawati (Poltekkes Kemenkes Semarang, 2019)
Background: One of the causes of puerperal infection can start from the perineal wound which is not treated properly. The management of perineal wounds can be done pharmacologically and non-pharmacologically. One of non-pharmacological management is by using breastmilk as a topical agent because it contains anti-inflammatory molecules, bioactive substances and growth factors which are very useful for wound healing and prevent infection. Purpose: This study aims to determine the effect of breastmilk topical of perineal wound healing on 1-7 days of postpartum mother in Mangkubumi Health Center of Tasikmalaya. Methods: This research was a Static Group Comparison design with the pre-experimental approach. The population in this study was 70 mothers who gave birth in December 2018 - February 2019 in Mangkubumi Health Center. The sampling technique in this study used purposive sampling and obtained as many as 60 people. Results: The results showed a good wound healing process can be seen in the intervention group at the end of the assessment as many as 66.7% and 33.3% showed insufficient wound healing. Different from the control group that showed 36.7% of good wound healing and 63.3% showed insufficient wound healing. Chi-square test showed a significant difference with ρ-value (0.039) α (0.05). Conclusion: The Effect of breastmilk topical of perineal wound healing on 1-7 days of postpartum mothers was evidenced. This study can be a reference for knowledge improvement in subsequent research.